Pengaruh Job Crafting terhadap Work Engagement pada Karyawan Divisi Marketing Falcon Pictures - Devri Nugraha Ihsan; Lisa Widawati; Ayu Tuty Utami (Jurnal Riset Psikologi, 2024)
Abstract. Job crafting is an effort made actively by individuals to balance job demand and job resources. Through job crafting efforts, work engagement can increase, resulting in good work productivity. This research aims to find out how much influence job crafting has on work engagement among Falcon Pictures marketing division employees. The research method used was quantitative with the number of subjects being 35 employees of the Falcon Pictures marketing division. This research uses the Job Crafting Scale (JCS) measuring instrument from Tims et al., (2012) which has been adapted by Astuti A. (2023) and the Utrecht Work Engagement Scale (UWES) measuring instrument from Schaufeli & Bakker which has been adapted by Aryanti et al. al., (2020). The research results found that 97.1% of Falcon Pictures marketing division employees had high job crafting and 97.1% of Falcon Pictures marketing division employees had high work engagement. In this study, job crafting had a significant influence on work engagement of 71.2%. The results of decreasing hindering job demands have the highest significant influence on work engagement of Falcon Pictures marketing division employees. Abstrak. Job crafting merupakan upaya yang dilakukan secara aktif oleh individu untuk menyeimbangkan job demand dan job resources. Melalui upaya job crafting, work engagement dapat meningkat sehingga menghasilkan produktivitas kerja yang baik. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh job crafting terhadap work engagement pada karyawan divisi marketing Falcon Pictures. Metode penelitian yang digunakan adalah kuantitatif dengan jumlah subjek 35 karyawan divisi marketing Falcon Pictures. Penelitian ini menggunakan alat ukur Job Crafting Scale (JCS) dari Tims et al., (2012) yang telah diadaptasi oleh Astuti A. (2023) dan alat ukur Utrecht Work Engagement Scale (UWES) dari Schaufeli & Bakker yang telah diadaptasi oleh Aryanti et al.,(2020). Hasil penelitian ditemukan 97,1% karyawan divisi marketing Falcon Pictures memiliki job crafting yang tinggi dan 97,1% karyawan divisi marketing Falcon Pictures memiliki work engagement yang tinggi. Pada penelitian ini job crafting memiliki pengaruh signifikan terhadap work engagement sebesar 71,2%. Hasil decreasing hindering job demands memiliki pengaruh signifikan paling tinggi terhadap work engagement karyawan divisi marketing Falcon Pictures.